Mantle velocity variations under the northern Canadian Cordillera through body wave tomography - Khare, Aditya U., author; Schutt, Derek, advisor; Buchanan, Kristen, committee member; Egenhoff, Sven, committee member (Colorado State University. Libraries, 2019)
The Mackenzie Mountains (MM) in the northern Canadian Cordillera (NCC) are an actively uplifting mountain range and an excellent location to investigate the causes of intra-plate orogeny. The orogen is situated almost ~750 km inboard of the active Pacific plate boundary, and little deformation is occurring between the MM and the Pacific Coast, except within the Coast Ranges. To investigate the causes of this orogeny, the Mackenzie Mountains Earthscope Project (MMEP) deployed 40 broadband seismographs and 4 continuous GPS instruments in a linear array from near the Pacific Coast to the Slave craton. Here we present results of teleseismic body wave tomography in the NCC that were obtained by using data from 37 of these MM stations as well as 67 other stations in the region surrounding the MM. Results show a sharp sub-vertical transition between low velocity in the Cordillera (ΔV -2%) and high velocity in the craton (ΔV +2%) about 100 km southwest of the Mackenzie River. The locations of Miocene to Present volcanism in the region also coincide well with the low velocity zones suggesting the presence of melt and/or anomalous temperatures. Two notable high velocity anomalies are seen beneath the Cordillera. The first is present under the Tintina Fault (ΔV +1.5%) and may be indicative of a lower crustal compositional anomaly. The other is at 600 km depth below the Cordillera (ΔVp +2%) which we interpret as delaminated lithosphere. The delamination possibly resulted from mantle upwelling due to the opening of the slab window ~20 Ma.